13=5+3b-1

Simple and best practice solution for 13=5+3b-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13=5+3b-1 equation:


Simplifying
13 = 5 + 3b + -1

Reorder the terms:
13 = 5 + -1 + 3b

Combine like terms: 5 + -1 = 4
13 = 4 + 3b

Solving
13 = 4 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
13 + -3b = 4 + 3b + -3b

Combine like terms: 3b + -3b = 0
13 + -3b = 4 + 0
13 + -3b = 4

Add '-13' to each side of the equation.
13 + -13 + -3b = 4 + -13

Combine like terms: 13 + -13 = 0
0 + -3b = 4 + -13
-3b = 4 + -13

Combine like terms: 4 + -13 = -9
-3b = -9

Divide each side by '-3'.
b = 3

Simplifying
b = 3

See similar equations:

| y2=16/64 | | -5.3b-15.16=-5.1b-11.72 | | 25200*(1/4) | | 7T+18-7=41 | | 2.5t-t=3+105t | | 9-1/2=5+4n | | 35-x=2/5x | | 3p-45=-20 | | 7x+8x-40=80-5x | | x+7x=56 | | -5(7y+9)= | | 3(x+5)+4x=-360 | | 5h+36=61 | | 7+(-20)= | | 2(-4-13)=37-8h | | y=x-14x+40 | | 255*(5/3) | | x-(-27)=39 | | 2/5x=35-x | | -5.7k+13.77=-7.7k-3.43 | | x+86=3x-36 | | 3*30+42h+195=390 | | 1*(5/3) | | 4(-7)+13=-9-3(-7+9) | | 12h+4.5=8.1 | | 14(7x-8)=5x-4 | | 3(1/21)=x | | -6+7x=-(3-7x)+2 | | 11-7X=47-35X | | 154228*(3/4) | | n-25=-45 | | 12.7y-17.2=13.7y |

Equations solver categories